2004
DOI: 10.1002/iroh.200410764
|View full text |Cite
|
Sign up to set email alerts
|

Yeast and Macroinvertebrate Communities Associated with Leaf Litter Decomposition in a Second Order Stream

Abstract: The composition of yeast and macroinvertebrate communities was studied on black alder, blue gum eucalyptus and English oak leaves decaying in a stream during a six-month period. ANOVA analysis showed significantly different values (p < 0.0001) of yeast and macroinvertebrate densities among the three leaf litters. Some yeast species such as Cryptococcus albidus (SAITO), C. laurentii (KUFFERATH), Rhodothorula glutinis (FRESENIUS), R. colostri (CASTELLI), and Debaryomyces hansenii (LODDER and KREGER-VAN RIJ) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…Bacteria become more important in the latter stages of litter decomposition, but their contribution to microbially driven litter mass loss is generally low (up to 14% [27,31]). Less information is available on the roles of yeasts, zoosporic fungi, oomycetes, and protists, but they were found to be associated with decomposing leaf litter and can affect litter decomposition directly or indirectly via trophic interactions [32][33][34][35][36]. The role of algae on litter decomposition is also uncertain with some studies suggesting that they can stimulate litter decomposition via microbial priming (i.e., the stimulation of microbial decomposers' activity by the addition of labile carbon) [37], while other studies found inhibition or no effect [38,39].…”
Section: Phases and Key Playersmentioning
confidence: 99%
“…Bacteria become more important in the latter stages of litter decomposition, but their contribution to microbially driven litter mass loss is generally low (up to 14% [27,31]). Less information is available on the roles of yeasts, zoosporic fungi, oomycetes, and protists, but they were found to be associated with decomposing leaf litter and can affect litter decomposition directly or indirectly via trophic interactions [32][33][34][35][36]. The role of algae on litter decomposition is also uncertain with some studies suggesting that they can stimulate litter decomposition via microbial priming (i.e., the stimulation of microbial decomposers' activity by the addition of labile carbon) [37], while other studies found inhibition or no effect [38,39].…”
Section: Phases and Key Playersmentioning
confidence: 99%
“…In one hand, field experiments have shown reduced diversity, density, and biomass of invertebrates, especially detritivores, in streams receiving eucalypt leaf litter (ABELHO and GRAÇA, 1996;LARRAÑAGA et al, 2006) or in experiments on leaf litter colonization (BASAGUREN and POZO, 1994;SAMPAIO et al, 2004). On the other hand, there is evidence from laboratory experiments that some shredders feeding on E. globulus leaves fail to grow (CANHOTO and GRAÇA, 1995).…”
Section: Introductionmentioning
confidence: 96%
“…The SP content differed between alder and oak ( p < 0.001) and between alder and plane ( p < 0.01), and whatever the treatment, reached higher values in microcosms with alder leaves. This might be related to the fact that alder leaves are colonized faster by microorganisms . Although the differences were not significant between treatments with or without fecal access, in all litters leaching was less expressive in the latter situation, probably due the general higher crayfish leaf consumption observed in the absence of fecal pellets.…”
Section: Discussionmentioning
confidence: 77%